2003
DOI: 10.1007/s00737-003-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and prevalence of depression in women 45?55 years of age visiting gynecological clinics in Poland

Abstract: The aims of the Polish survey were to assess efficacy of screening for depression in gynecological practice and to estimate prevalence of depressive disorders in midlife women visiting gynecologists. The study included 2262 female outpatients aged 45-55, who were screened by 120 gynecologists throughout Poland. Patients completed the Beck's Depression Inventory (BDI) and were assessed by gynecologists to verify the presence of symptoms of a current Depressive Episode according to ICD-10 diagnostic criteria. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
1
2
1
6
Order By: Relevance
“…Hortal et al 14 noted MD prevalence of 26.8% among women receiving primary care. Compared with studies that have assessed menopausal women receiving outpatient care, our study noted higher MD prevalence than the study by Wojnar et al 15 (19%) and lower than the study by Hay et al (45%) 3 and Anderson et al, 16 who found 33% of patients with moderate to severe MD. Therefore, the tendency of higher prevalence of mental disorders among outpatient menopausal women, in relation to women receiving general care, was also seen in our study.…”
Section: Discussioncontrasting
confidence: 87%
“…Hortal et al 14 noted MD prevalence of 26.8% among women receiving primary care. Compared with studies that have assessed menopausal women receiving outpatient care, our study noted higher MD prevalence than the study by Wojnar et al 15 (19%) and lower than the study by Hay et al (45%) 3 and Anderson et al, 16 who found 33% of patients with moderate to severe MD. Therefore, the tendency of higher prevalence of mental disorders among outpatient menopausal women, in relation to women receiving general care, was also seen in our study.…”
Section: Discussioncontrasting
confidence: 87%
“…The most common general comorbidities were high blood pressure, ischemic diseases, hypothyroidism, other thyroid disorders, and diabetes. The fact that comorbidities were highly significant for light and severe depression stands out as confirming the data in the literature [25,26]. …”
Section: Discussionsupporting
confidence: 85%
“…Tem sido sugerido que, com o avançar da idade, os escores de QVRS reduzam de forma mais acentuada em mulheres, presumivelmente devido às alterações hormonais e à depressão 20,21 . Por esta razão, também comparamos os escores de QVRS de homens e mulheres em dois grupos etários: 18 a 49 e ³ 50 anos.…”
Section: Discussionunclassified